Efficiency of tourist and recreational complex as a factor of territorial development (in case of Russian Azov sea coast) - Ksenia Vladimirovna Kushnir; Olga Vasilyevna Ivliyeva (Наука. Инновации. Технологии)
In case of modern geopolitical and economic conditions the tourist and recreational complex can act as the effective platform in realization and advance of tourist and recreational capacity of territory. The article defines the criteria and assesses the indicators of the level of tourism development and social-economic well-being of the municipal areas of the Eastern Priazovye by technique of the multidimensional comparative analysis with mathematical methods of standardization indicators. It was identiied the areas with a high level of tourism development and the areas that require the revitalization of the tourism industry. According to results, it can be argued that all areas of the Russian Azov Sea coast have high levels of social-economic well-being. In conclusion it was determinate that all municipal areas of the Russian Azov Sea coast have necessary social and economic conditions for development of tourist branch. In paper also used GIS-technologies for visualization of modern results. In conclusion were offered types of tourism which are expedient for developing on each group.